How to assess chemical oxidation efficiency - Bertanza, G (Water science and technology : a journal of the International Association on Water Pollution Research, 2004)
In this work, a real wastewater (deriving from the chemical-pharmaceutical field) was treated by means of H2O2/UV process under different conditions in a pilot-scale plant. Several methods were used in order to assess the oxidation efficiency and to understand the main reaction features. It was shown that non-conventional COD measurement (with a 75 degrees C digestion of the sample) is helpful for understanding reaction mechanisms, when integrated with TOC and COD analyses and GC-MS determinations. For the biodegradability study, beside BOD (5 and 20 days) measurements, OUR and AUR tests provide additional information especially when wastewater is tested by taking the activated sludge from the treatment plant which should really be fed with it. Finally, dehydrogenase activity measurements can show the presence of complex organic matter, which may be degraded only by an acclimated biomass